THE INFLUENCE OF REFERENCE GROUPS, FAMILY, ROLES AND STATUS ON CONSUMER PURCHASE INTENTION OF COUNTERFEIT WATCHES IN MANADO - Pesik, Michael .; Lapian, Joyce .; Tumewu, Ferdinand . (FEB Universitas Sam Ratulangi Manado, 2017)
Abstract: The objective of this study is to understand the influence of reference groups, family, and roles & status consumer purchase intention of counterfeit watches in Manado. The data was collected from 100 respondents that purchase counterfeit watches and multiple regression analysis was used to test the relationship among variables. The result reveales that Role and Status have significant influence to the consumer purchase intention of buying counterfeit watches in Manado. This characteristic gives a big influence to the retailer of original product for to hold the retailer of counterfeits sells. The author recommends to original brand company or retailer should improve their knowledge about how to attract the intention of consumer in manado to consume original product. Businesses have to spend their concern to give customer who just purchase from their shop or services to give them enchantment after from the shop. Also find out some strategy and tactics to keep selling original product without making the consumer think the product is too expensive, thus making them buy alternative goods which is nothing but counterfeit goods.ÂÂKeywords: Counterfeiting, Counterfeit Shoes, Reference Group, Family, Roles and Status, Consumer Purchase Intention